PENYISIHAN KEKERUHAN PADA SISTEM PENGOLAHAN AIR SUNGAI TEMBALANG DENGAN TEKNOLOGI RAPID SAND FILTER - Catur Pamularsih; Dera Choanji; I Nyoman Widiasa (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Design of rapid sand filters differ from one place to another because it has the distinction of influent. Therefore in order to obtain the optimal, effective and efficient design for water treatment tembalang river so that the effluent can be used around the community. The purpose of this study is to get a pattern of rapid sand filter operation with water from  Tembalang river. Variables used in this study is the loading rate (10, 11, 12 gpm/ft2), high media filter (60 and 100 cm), and the addition of coagulant. The result of study showed 85% reduction of turbidity by using a loading rate of 10.2 gpm/ft2 at height of 100 cm filter media. At loading rate 11.75 gpm/ft2 removal turbidity by using a coagulant will be more effective when compared to not using coagulants.